Penerapan Pembelajaran Berbasis Masalah Untuk Meningkatkan Komunikasi dan Aktivitas Matematika Siswa Sekolah Dasar - Erika, Erika; Rambe, Juli Asmida (LPPPI Publishing, 2024)
This study aims to determine: (1) To see the difference in the ability of communication the students who were given a mathematical problem-based learning approach (2) To see / know the active activity of students in problem-based learning approach This study was a quasi-experimental research. The study population 101766 primary school students Bandar Setia class V. The sample selection is done randomly. The instrument used consisted of: (1) test mathematical communication skills (2) The student activity observation, tests used in this study is the description. The instrument has qualified content validity and construct validity and reliability coefficient of 0.966 for mathematical communication skills of students. The data in this study were analyzed using descriptive statistical analysis and inferential analysis. Descriptive analysis is intended to describe the activities of students in each lesson in learning and problem-based approach to learning with conventional approach. Inferential analysis of data performed by the independent samples t test. The results showed that: (1) mathematical communication skills of students who are taught by the PBM approach higher than students taught by a conventiona approach. It can be seen from the average score is 44.93 PBM approach; and the average score is 38.37 contextual. It can also be seen from the results of the t test is for mathematical communication skills of students is 7.423, while the table = 2:00, and (2) The level of student active activity where students who receive PBM learning is at the tolerance limit determined by the number of successful actions for aspects of student activity above SR ³ 80% are within ideal category.